The land beyond the border: state formation and territorial expansion in Syria, Morocco, and Israel - Becke, Johannes (SUNY Press, 2021)
"Uses an innotvative theoretical framework to comparatively explore the dynamics of state expansion and contraction in Syria (1976-2005), Morocco (since 1975), and Israel (since 1967)"--
Revision of author's thesis (doctoral)
Literaturverzeichnis: Seite 36-44, Literaturhinweise, Register
Keywords: Syria -- Territorial expansion; Morocco -- Territorial expansion; Israel -- Territorial expansion; Hochschulschrift; Internationaler Vergleich; Expansionspolitik; Gründung; Staat; Postkolonialismus; Israel; Marokko; Syrien